Genome-Wide Analysis of the Cytochrome P450 Gene Family Involved in Salt Tolerance in Gossypium hirsutum - Sun, Kangtai; Fang, Hui; Chen, Yu; Zhuang, Zhimin; Chen, Qi; Shan, Tingyu; Khan, Muhammad Kashif Riaz; Zhang, Jun; Wang, Baohua (Frontiers in Plant Science, 2021)
Plant cytochrome P450 (P450) participates in a wide range of biosynthetic reactions and targets a variety of biological molecules. These reactions lead to various fatty acid conjugates, plant hormones, secondary metabolites, lignin, and various defensive compounds. In our previous research, transcriptome analysis was performed on the salt-tolerant upland cotton “Tongyan No. 1”. Many differentially expressed genes (DEGs) belong to the P450 family, and their domains occur widely in plants. In this current research, P450 genes were identified in Gossypium hirsutum with the aid of bioinformatics methods for investigating phylogenetic relations, gene structure, cis-elements, chromosomal localization, and collinearity within a genome. qRT-PCR was conducted to analyze P450 gene expression patterns under salt stress. The molecular weights of the 156 P450 genes were in the range of 5,949.6-245,576.3 Da, and the length of the encoded amino acids for all the identified P450 genes ranged from 51 to 2,144. P450 proteins are divided into 4 different subfamilies based on phylogenetic relationship, gene structure, and chromosomal localization of gene replication. The length of P450 genes in upland cotton differs greatly, ranging from 1,500 bp to 13,000 bp. The number of exons in the P450 family genes ranged from 1 to 9, while the number of introns ranged from 0 to 8, and there were similar trends within clusters. A total of 31 cis-acting elements were identified by analyzing 1,500 bp promoter sequences. Differences were found in cis-acting elements among genes. The consistency between qRT-PCR and previous transcriptome analysis of salt tolerance DEGs indicated that they were likely to be involved in the salt tolerance of cotton seedlings. Our results provide valuable information on the evolutionary relationships of genes and functional characteristics of the gene family, which is beneficial for further study of the cotton P450 gene family.